Pengetahuan dan Dukungan Keluarga dengan Self Care pada Pasien TB Paru - Halawa, Dian Kasih Putri; Novriani, Eva; Salsabila, Nona Nur; Sibagariang, Leonni Jessica; Maisari, Maisari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the relationship between knowledge and family support with self-care in pulmonary TB patients at Wulan Windy Hospital. The quantitative method uses an analytical survey design with a cross-sectional study design. The results of the study, statistical tests obtained a p-value of 0.022, meaning that there is a relationship between knowledge and self-care in pulmonary TB patients, and a p-value of 0.002, which means that there is a relationship between family support and self-care in pulmonary TB patients. The conclusion is that lack of knowledge and family support results in the application of self-care in pulmonary TB patients will also be lacking. Keywords: Family Support, Knowledge, Self-Care, Pulmonary TB